2021
DOI: 10.1002/jhbp.1067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative complications and long‐term oncological outcomes in minimally invasive versus open pancreatoduodenectomy for distal cholangiocarcinoma: A propensity score‐matched analysis

Abstract: Background Pancreatoduodenectomy (PD) is the only curative therapy for distal cholangiocarcinoma (dCC). There has been no study to compare outcomes between minimally invasive pancreatoduodenectomy (MIPD) and open pancreatoduodenectomy (OPD) for dCC. The aim of the study is to compare the two operation types for dCC in terms of postoperative and oncologic outcomes. Methods Data from 426 patients who underwent MIPD (n = 91) or OPD (n = 335) for dCC from January 2012 to December 2019 at two tertiary hospitals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Several studies have shown that LPD and OPD have similar long-term survival rates in the treatment of pancreatic and periampullary cancers (15,27). A recently published paper showed that there was no significant difference in long-term survival between LPD and OPD in DCC (30). In contrast, our research revealed that the prognosis for LPD was improved.…”
Section: Discussioncontrasting
confidence: 44%
“…Several studies have shown that LPD and OPD have similar long-term survival rates in the treatment of pancreatic and periampullary cancers (15,27). A recently published paper showed that there was no significant difference in long-term survival between LPD and OPD in DCC (30). In contrast, our research revealed that the prognosis for LPD was improved.…”
Section: Discussioncontrasting
confidence: 44%
“…Effect sizes were presented as mean differences with a 95% CI. The random‐effects model was used for pooling analysis to compensate for the heterogeneity of studies [ 23 , 24 ] statistics. In this regard, I2 ≥ 50% and ≥75% indicated substantial and considerable heterogeneity [ 24 ] study removal method to the subanalysis to assess whether any individual study exerted particular influence on the overall effect size [ 25 , 26 ]; p‐values < 0.05 were considered statistically significant.…”
Section: Reviewmentioning
confidence: 99%
“…All three studies report similar findings regarding long-term outcomes. Uijterwijk et al [ 23 ] and Kim et al [ 24 ] suggest that MIPD is comparable to OPD in terms of long-term outcomes, while Xu et al [ 25 ] indicates no significant differences in long-term survival between RPD and OPD groups.…”
Section: Reviewmentioning
confidence: 99%
“…Based on the results, the criteria of MIPD have expanded and MIPD showed similar oncologic outcomes when compared with open PD. 5,6 Thus, MIPD was shown to be an acceptable procedure in terms of clinical and oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated the safety and feasibility of MIPD by comparing it with open pancreatoduodenectomy (PD). Based on the results, the criteria of MIPD have expanded and MIPD showed similar oncologic outcomes when compared with open PD 5,6 . Thus, MIPD was shown to be an acceptable procedure in terms of clinical and oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%